IMPLANTATION OF LHRH-a HORMONE TO STIMULATION OF GONAD DEVELOPMENT OF HUMPBACK GROUPER SECOND GENERATION ( F-2 ) - Tridjoko Tridjoko (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2013)
This study aimed to determine the effect of LHRH-a hormone implantation on gonadal development of humpback grouper, Cromileptes altivelis 2nd generation (F-2). Individuals used were 20 female grouper fish with weight range of 600-800 gram/fish and total length range of 28.0-30.0 cm. The treatment used 5 fish each with tagging. Grouper fishes were stocked into the 75 m3 circular concrete tank. Hormone of LHRH-a with dosage of 50 μg/kg body weight was used as implant treatment of (A) 1 time,, (B) 2 times, (C) 3 times, and (D) without implant. The results showed that implantation of LHRH-a hormone were significantly stimulate gonad development of humpback grouper second generation (F-2). Treatment of 3 times implant every month showed the best results produced oocyte diameter up to 480 μm, while the control of oocyte diameter only reached <400 μm. Keywords: LHRH-a hormone, implantation, Humpback grouper, gonad development